2004
DOI: 10.17305/bjbms.2004.3463
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of risk factors for cervical cancer among women in fertile age

Abstract: Cervical and breast cancer are usually type of tumor that are found among women in fertile age in Bosnia and Herzegovina. Final goal was to establish frequency of risk factors that are responsible for development of those types of cancer as well as establish possibility of prevention, according to the existence of each risk factor. Research was conducted through out surveys among women which were selected by accident. The amount of questioned women is 200, and out of that number 70 (35%) were out of rural envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…12 Over 50% of women of fertile age in B&H do not visit a gynecologist regularly, although the high incidence of gynecological infections and high incidence of breast cancer and cervical cancers. 34 Some studies have confirmed the importance of education as factors associated with preventive practices, to regular gynecological examinations, and screening tests. 32 J Pizarro and al.…”
Section: Discussionmentioning
confidence: 99%
“…12 Over 50% of women of fertile age in B&H do not visit a gynecologist regularly, although the high incidence of gynecological infections and high incidence of breast cancer and cervical cancers. 34 Some studies have confirmed the importance of education as factors associated with preventive practices, to regular gynecological examinations, and screening tests. 32 J Pizarro and al.…”
Section: Discussionmentioning
confidence: 99%